Carcass Productivity and Meat Quality Bambu Apus Rabbit - H. Margatama; H. Nuraini; B. Brahmantiyo; Supratikno (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2023)
Rabbits are meat-producing livestock with high productivity. Rabbit meat has high nutritional content and is good for health. The DKI Jakarta Government through the Center for Animal Health and Livestock Services (Pusyankeswannak) has opened the Bambu Apus Livestock Park. This research was conducted to determine the productivity of bambu apus rabbit carcasses as broiler rabbits to support urban farming programs in DKI Jakarta. Ten of bambu apus rabbits (five males and five females), ten of new zealand white rabbits (eight males and two females) and 17 rexsi grinak rabbits (eight males and nine females) were used. The body weights of the rabbits ranged from 2000 to 3000 g per head. This research has obtained Ethical Clearance (Balitbangtan/Center for Animal Husbandry Research BRIN/NRm/01/2022). Rabbits were slaughtered according to Islamic Syar’i and the carcass were cutting according to the commercial cut. A completely randomized design with a 3 x 2 factorial pattern (sex and type of rabbit) was used with carcass productivity and meat physical properties as variables. Bambu apus rabbits have good carcass productivity (Carcass Percentage, Meat Bone Ratio), meat on commercial cuts (Loin and Hindleg) and carcass quality (pH, tenderness, Water Holding Capacity and cooking losses) which were the same as new zealand white rabbits and rexsi agrinak rabbits as the broiler rabbit. Bambu apus rabbits have good carcass production and carcass meat quality so they have the potential to be developed into broiler rabbits in support of urban farming programs.